Vehicle movement on the road network between urban centers in Al-Mada’in district in 2019-2020 - Ali, Bashar Jebur; Al-Howaider, AbdulRahman Jery (Al-Adab Journal, 2021)
The research aims to analyze the reality of vehicle movement on the road network between urban centers in Al-Madaen district, by monitoring the number of vehicles movement, and for the different types, sizes and capacities of vehicles required converting the load vehicles into a coefficient equivalent to standard vehicles, and the study compared the carrying capacity of the roads with the reality of the situation, as it showed The results of the field survey and the presence of a high density of vehicle movement on the road linking the Madaen district center and the bridge district exceeds the road capacity during the three peak hours of the official working days, as the total trips reached (42182.5) vehicle / standard, and the total trips for official holidays reached (13298.25) vehicles. / Standard , While the traffic movement on the road linking Al Wahda side and the bridge side showed that there is a high density that exceeds the capacity of the road, as the total number of trips for the three peak hours of the official working days reached (58031.25) vehicle / standard, and the total trips for the three peak hours for official holidays reached (54313.5) 1) vehicle / standard, and the study found that there is a high traffic density on the road linking the Al Madaen district center and the unit area that exceeds the capacity of the road, as the total number of trips for the three peak hours reached (18413.5) vehicles / standard, while the traffic movement was for the official holidays of the three peak hour (16180.25) vehicle / standard, The analysis of the total field monitoring of vehicle movement in the cities of Al-Mada’in found a high density exceeding the capacity of the roads, during the official working days and the three peak hours, it reached (118627.25) vehicles / standard, and for official holidays it reached (83792) vehicles / standard, so it requires planning and distribution of roads, to create New traffic axes that accommodate traffic density, and the study applied the indicator of density of traffic volume in relation to (number of population, length of roads, area area) served, as it was proved that there is a high density that causes hotspots of traffic congestion, due to the lack of movement axes, so it requires choosing suitable solutions for the available capabilities.